Member - Masouras, Panicos (My University, 2026)
I have been reviewing papers as part of the process for accepting papers for the conference. I have been disseminating and promoting the conference within my network. Advising the committee chair on topics and themes to be included in the call for papers. You may see the 2021 link of committee members: http://www.icetc.org/tc.html